Reaction norms for the study of genotype-environment interaction for growth and indicator traits of sexual precocity in Nellore cattle - Lemos, M. V. A. [UNESP]; Chiaia, H. L. J. [UNESP]; Berton, M. P. [UNESP]; Feitosa, F. L. B. [UNESP]; Aboujaoude, C. [UNESP]; Venturini, G. C. [UNESP]; Oliveira, H. N. [UNESP]; Albuquerque, L. G. [UNESP]; Baldi, F. [UNESP] (Funpec-editora, 2015)
The objective of this study was to quantify the magnitude of genotype-environment interaction (GxE) effects on age at first calving (AFC), scrotal circumference (SC), and yearling weight (YW) in Nellore cattle using reaction norms. For the study, 89,152 weight records of female and male Nellore animals obtained at yearling age were used. Genetic parameters were estimated with a single-trait random-regression model using Legendre polynomials as base functions. The heritability estimates were of low to medium magnitude for AFC (0.05 to 0.47) and of medium to high magnitude for SC (0.32 to 0.51) and YW (0.13 to 0.72), and increased as the environmental gradient became more favorable. The genetic correlation estimates ranged from 0.25 to 1.0 for AFC, from 0.71 to 1.0 for SC, and from 0.42 to 1.0 for YW. High Spearman correlation coefficients were obtained for the three traits, ranging from 0.97 to 0.99. The reaction norms along the environmental gradient of 10 sires each with the highest or lowest breeding value for YW predicted by single-trait analysis demonstrated more plastic phenotypes for YW and more robust phenotypes for SC. The effect of GxE was most important for YW and AFC with respect to SC. When animals are selected for higher SC or YW or lower AFC, considering or not the GxE effect, it is expected that the same animals will be selected. The reaction norms obtained based on sire breeding values along the environmental gradient showed that animals with extreme breeding values respond differently as environmental conditions improve.
Keywords: Beef cattle; Legendre polynomials; Scrotal circumference; Yearling weight